Percepción de actores locales sobre implicancias de la focalización en el Valle del Mantaro - Chanca Flores, Aparicio (2020)
The Household Targeting System (in Spanish, SISFOH) is a process for determining the Socioeconomic Classification (SEC), which certifies vulnerable people and population groups, inmersed in poverty or extreme poverty, in the face of state social programs and subsidies. The research’s objective is to show the perception that local actors have about the implications of targeting in Mantaro Valley. It is a basic type and descriptive lever research, it has as analysis units non-beneficiary residents of eight districts that are part of the four provinces of Mantaro Valley. Were surveyed 384 persons over 15 years-old, with an Likert scale. Data analysis was performed in software SPSS 25.0, obtaining as a result that the vast majority have a negative perception of the SISFOH, because they observe some limitations of inclusion and exclusion in the registry and certification.